Analysis of Adolescents’ Sexual Orientation in Bendungan Hilir Sub District Central Jakarta in 2022 - Silawati, Vivi; Lena, Epi; Azzahroh, Putri (Rajaki of Tulip Medika Publisher, 2023)
Background: Adolescence is considered as the peak of a process to find one's self-identity and sexual orientation more specifically, whether as heterosexual, homosexual, or as bisexual. Among the social problems that occur in adolescents is LGBT whose population in the world continues to increase, according to a survey by the Center for Intelligence Agency (CIA). The number of LGBT population in Indonesia is the 5th largest in the world after China, India, Europe and America. It is estimated that 3 percent of Indonesia's population are LGBT people or around 7.5 million people. Objective: This study aims to find indicators and variables that cause sexual orientation in adolescents (women like women) in Central Jakarta in 2022. Methodology: This study is a qualitative research design with a case study approach to informants who are lesbians. Collecting data using interview guides, uninvolved observation, and documentation. The data were processed using content analysis using a matrix and presented in a narrative manner. Results: The results showed that there were 11 variables with each indicator that led to sexual orientation in adolescents, including personality, perception, attitude, religion, parenting style, social support, intensity of access to pornography, sexual behavior, trauma and environment. Conclusions and suggestions: Parenting and trauma variables that are very prominent in lesby sexual orientation, the family plays an important role in the growth and development of adolescents.